The Intersection of Global Legal Frameworks and Islamic Judicial Principles in Post-Conflict Reconstruction and Peace building - Suhaba Nizar Nazem; Ammar Khadim Jasim; Mohammed Turki; Oudha Yousif Salman Al-Musawi; Dmytro Khlaponin (Al-Istinbath: Jurnal Hukum Islam)
The article explores the integration of international law and Islamic judicial principles in post-conflict reconstruction to foster long-term peace. The research aims to assess how these legal frameworks contribute to governance, human rights, and reconciliation in societies recovering from war. Utilizing a qualitative methodology, the study analyzes case studies and legal documents to examine the effectiveness of combining international and Islamic legal systems in addressing post-conflict challenges. The findings reveal that while international law provides a foundation for accountability and normative standards, its universal application often neglects local traditions and culturally rooted dispute-resolution processes critical for sustainable peace. By incorporating Islamic judicial principles, which emphasize justice, reconciliation, and community involvement, these gaps can be addressed effectively. The study concludes that the integration of Islamic judicial concepts with international legal norms offers a culturally sensitive approach to rebuilding post-conflict societies, enhancing local ownership and sociopolitical alignment. This nuanced framework holds the potential to strengthen governance structures and promote enduring peace.